2021
DOI: 10.1111/jog.14728
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound fetal shoulder soft tissue thickness measurement in estimation of fetal weight

Abstract: Aims Birth weight (BW) estimation with ultrasound is of great importance in delivery decision and management of complications of delivery. The aim was to evaluate the effect of femur, humerus, and clavicular soft tissue thickness on BW and developed a formula for proper estimation of fetal weight. Methods This prospective cohort study, included 231singleton pregnancies, with 34 and 42 weeks of gestation, delivered within 48 h after ultrasound examination. In addition to four biometric ultrasound measures, shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The most objective method currently employed to estimate fetal body weight is ultrasonographic (US) measurement which encompasses over 30 different formulas for the US estimates to predict newborn birth weight [16][17][18] , with the most widely used being the Hadlock formula 19 . To generate sonographic fetal weight estimations with a lower error margin, many formulas have re ected disparate parameters of the fetus (fetal abdominal fat layer 20 , shoulder soft-tissue thickness 21 , biacromial diameter 22 ), and some have even entailed 3D sonographic measurements 23 . Although such formulas and novel predictors may improve the accuracy of US evaluation, they nevertheless increase technical di culty and sonication time.…”
Section: Discussionmentioning
confidence: 99%
“…The most objective method currently employed to estimate fetal body weight is ultrasonographic (US) measurement which encompasses over 30 different formulas for the US estimates to predict newborn birth weight [16][17][18] , with the most widely used being the Hadlock formula 19 . To generate sonographic fetal weight estimations with a lower error margin, many formulas have re ected disparate parameters of the fetus (fetal abdominal fat layer 20 , shoulder soft-tissue thickness 21 , biacromial diameter 22 ), and some have even entailed 3D sonographic measurements 23 . Although such formulas and novel predictors may improve the accuracy of US evaluation, they nevertheless increase technical di culty and sonication time.…”
Section: Discussionmentioning
confidence: 99%
“…The most objective method currently employed to estimate fetal body weight is ultrasonographic (US) measurement, which encompasses over 30 different formulas for the US estimates to predict newborn birth weight [16][17][18], with the most widely used being the Hadlock formula [19]. To generate sonographic fetal weight estimations with a lower error margin, many formulas have reflected disparate parameters of the fetus (fetal abdominal fat layer [20], shoulder soft-tissue thickness [21], biacromial diameter [22]), and some have even entailed 3D sonographic measurements [23]. Although such formulas and novel predictors may improve the accuracy of US evaluation, they nevertheless increase technical difficulty and sonication time.…”
Section: Discussionmentioning
confidence: 99%
“…validated Scioscia's formula and proposed a modified one, both of which were considered equally efficient in calculating true fetal weight. For macrosomia or diabetic gestations, the utility of STT was valuable 62,63 . Garabedian et al 63 .…”
Section: How To Establish a Chinese Fetal Growth Standardmentioning
confidence: 99%
“…For macrosomia or diabetic gestations, the utility of STT was valuable. 62,63 Garabedian et al 63 showed that soft tissue in the upper arm had the best area under receiver operating characteristic (AUROC) value (0.855) along with good sensitivity and specificity (85.7% and 80.0%, respectively) for detecting macrosomia in pregnancies complicated by diabetes.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation